Applied behavior analysis advanced guidebook: a manual for professional practice - Luiselli, James K (Academic Press, 2017)
This manual gives behavioural practitioners pragmatic advice, direction and recommendations for being an effective clinician, consultant, supervisor and performance manager. It adopts a how to do it perspective featuring contributions from expert scientist-practitioners. Each chapter introduces the relevance of the topic for practicing professionals, describes and synthesises the empirical basis of the topic, and then presents practitioner recommendations. With this format, readers can navigate the chapters with familiarity and confidence to facilitate the understanding of content and integration of the many practice areas addressed.